PRE-DESIGN OF INTERCROPPING FARMING SYSTEM OF WATERMELON AND RED BEANS IN PEPPER PLANTATION LAND - Ivana Pudiyani, Pauline
This study proposes a preliminary design for an intercropping system combining watermelon (Citrullus lanatus) and red beans (Phaseolus vulgaris) in pepper (Piper nigrum) plantations using gamal (Gliricidia sepium) as live stakes. The primary objective of this research is to increase land use efficiency, reduce operational costs, and provide additional income for pepper farmers. The background of the study highlights that pepper is a major commodity in the Bangka Belitung Islands but requires optimal stakes for its growth. The use of dead stakes such as wood or concrete has disadvantages, such as high costs and short usage periods. Therefore, the use of live stakes like gamal can provide a more economical and sustainable solution. This research has three main objectives: (1) to design a biomass production system for watermelon and red beans using the intercropping method in pepper plantations, (2) to determine the mass and energy balance in this preliminary design, and (3) to conduct a financial feasibility study of this intercropping system. The methodology used involves the simultaneous cultivation of watermelon and red beans along with pepper and gamal on a 100 m² plot in Namang Village, Central Bangka. The area consists of open farmland that will be used for cultivating red watermelon, red beans, and pepper. The red watermelons will be planted in the center of the farm using a row planting system, while the red beans and peppers will be planted around them in an intercropping pattern to utilize space effectively. The production from this preliminary design includes 1920 kg/year of watermelon, 20.16 kg/year of red beans, 180 kg/year of pepper, and 347 kg/year of gamal. Analysis results indicate that this intercropping system can increase land productivity and provide additional income through the sale of watermelon and red bean produce. Pre-design of intercropping system for watermelon and red bean cultivation on pepper land has 3 subsystem stages, namely cultivation subsystem, pepper washing and soaking subsystem, and pepper drying subsystem. In the cultivation subsystem, there are 4 sub-subsystems divided based on each commodity type, namely watermelon, red bean, pepper plants, and gamal plants. The red bean commodity has a total mass balance of 221,283 kg/year, then the watermelon commodity has a total mass balance of 3.517,541 kg/year. Furthermore, the pepper commodity has a total mass balance of 340.775 kg/year and finally, the gamal commodity has a total mass balance of 530.16 kg/year. The pepper washing and soaking subsystem have a total mass balance of 680 kg/year. The pepper drying subsystem has a total mass balance of 72.79 kg/year. In the cultivation subsystem, human energy expenditure is 539,910 kJ/year for watermelon and red bean. In the cultivation subsystem, human energy expenditure is 422,677 kJ/year for pepper and gamal. In the washing and soaking subsystem is 3350.63 kJ/year, and in the pepper drying subsystem is 1,478.71 kJ/year. From a financial perspective, this study includes various analyses of costs and revenues. The fixed costs required are Rp9.132.000 per year, while variable costs amount to Rp148.800 per year, leading to a total operational cost of Rp9.276.800 per year. With gross revenue of Rp 37.427.500 per year, the study estimates a net profit of Rp 28.150.700 per year. The Break Even Point (BEP) analysis shows that the breakeven point for this project is Rp2.285.959. Additionally, the results show that the project has a Net Present Value (NPV) of Rp35.643.702 and an Internal Rate of Return (IRR) of 48%, indicating a high return on investment. The project's Net B/C Ratio is 2,06 meaning that the net profit obtained is more than twice the costs incurred. The Payback Period (PP) is estimated to be around 2 years 9 months, indicating that the investment will be recovered in a relatively short period. The final outcome of this study is expected to provide new knowledge on intercropping systems and serve as a reference for PT Cinquer Agro Nusantara and pepper farmers in Bangka Belitung to optimize the use of pepper plantation land more efficiently and sustainably.